BUDAYA AUSTRONESIA Dl KAWASAN DANAU SENTANI (Austroneslan Culture In the Sentani Lake Area) - Hari Suroto (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2016)
Pottery artifacts distribution and language show that Austroneslan speakers mostly settle, do activity, and interact with indigenous Papua In the coastal. Sentani Lake area is located in north part of Papua, in which Sentani language belongs to the non-Austronesian (phylum Trans New Guinea). This study is aimed to reveal the influence of Austroneslan culture in Sentani Lake area through descriptive and qualitative methods. The data is gathered by conducting surface survey, environmental observation, and ethnoarchaeological approach. The influence of Austroneslan culture in Sentani Lake area is brought through the coastal communities in Vanimo, Altape, and East Sepik Papua New Guinea. Artifacts as the evidences showing the influence of Austroneslan culture am in the form of pottery, glass bracelet, glass beads, and bronze artifacts. It is also shown through a pottery making tradition, tattoo, alcoholic drink, leadership system, and the breeding of dog, pig, and chicken. AbstrakPersebaran artefak gerabah dan bahasa menunjukan penutur Austronesia lebih banyak bermukim, beraktivitas, dan berinteraksi dengan penduduk asli Papua di pesisir. Kawasan Danau Sentani terletak di pesisir utara Papua, bahasa Sentani tergoiong dalam bahasa non-Austronesia (phylum Trans New Guinea). Tuiisan ini bertujuan untuk mengetahui pengaruh budaya Austronesia di Kawasan Danau Sentani. Tulisan ini menggunakan metode deskriptif kualitatif. Metode pengumpuian data dilakukan dengan survei permukaan tanah serta pengamatan lingkungan, serta perdekatan etnoarkeologi. Pengaruh budaya Austronesia di Kawasan Danau Sentani melaiui masyarakat pesisir di Vanimo, Aitape, dan Sepik Timur Papua Nugini. Aftefek yang menjadi bukti pengaruh budaya Austronesia yaitu gerabah, geiang kaca, manik-manik kaca, artefak pemnggu, Pengaruh iainnya yaitu tradlsi pembuatan gerabah, tradlsi tato, pembuatan minuman beralkohol, sistem kepemimpinan serta pemeiiharaan anjing, babi dan ayam.